PENGARUH LOKASI USAHA TERHADAP MINAT BELI KONSUMEN (STUDI KASUS PASAR SWALAYAN BOROBUDUR MANADO) - Garry Rondonuwu; Dantje Kelles; Lucky F. Tamengkel (JURNAL ADMINISTRASI BISNIS, 2016)
Abstract.The retail business is business activities of selling goods or services to individualsfor the purposes of self, family, or household. Buying interest is something related toconsumer plans to buy certain products, as well as how many units of the product is needed ata particular period. Examples of the research is the supermarket Borobudur Manado, which isone retail company that is egaged in the sale of products such as household appliances,school supplies and office, needs of infants and children, food, dirinks, slothing, beautyproducts and others. The purpose of this study was to determine the extent of the influence of the location of theconsumer purchase interest in the supermarket Borobudur Manado. In the face of the targetmarket the company has a set of marketing tools, marketing tools that can be grouped intofour groups of variables known as 4Ps, namely : Product (produk), Price (Harga), Where(tempat), and Promotion (Promosi). In this study, the study design used is descriptive-qualitative research for finding facts whitproper interpretation and the goal is to find a picture of systematic, factual, and accurate. Asfor the population in this study is all the customers who come to shop at the supermarketBorobudur Manado. The Study sample was taken 60 respondents, were taken randomly. Thetype of data used is primary and secondary data. To obtain primary data, consumer writer distributing questionnaires to 60 respondents. Thistesting is done using the Pearson Product moment (Pedoman suatu model) r table value canbe obtained where df=n-2, in this case is the number of samples or the repondent. Hypothesis testing using analytical models of multiple regression analysys (Multiple analisisberganda), namely : Test the coefficient of dtermination (R²) was conducted to determinehow much ability the dependent variable to explained by the independent variables. Teststatistic t use determines the presence or absence of variable influence of the independentindividual the dependent variable in the test at the 0,05 level, if the probability t is smallerthan 0,05 then Ho is accepted and rejects Ho. Whereas if the value of probability t is greaterthan 0.05 the Ho is accepted and Ha refused.  Key Words : Location and buying interest